Exploring Phytocompounds’ Interaction with Multi-Serotype Dengue Virus NS5-MTase: Insights into Binding Affinity and Activity - Alwabli, Afaf Salim; Balubaid, Mohammed; Tarique, Mohammed (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Dengue Virus (DENV) infection poses a formidable global health threat, spanning from mild breakbone fever to severe conditions such as dengue hemorrhagic fever and dengue shock syndrome. The NS5-MTase enzyme assumes a pivotal role in DENV replication by catalyzing methylation at guanine N7 and ribose 2'-OH during viral cap structure formation. Materials and Methods Targeting the MTase presents a promising strategy for combating flavivirus infections. In recent years, plant-derived metabolites have garnered attention for their antiviral properties, particularly flavones and flavonoids, which have shown efficacy against the DENV MTase protein. Results This study seeks to identify phytocompound capable of interacting with multiple DENV serotypes. Employing a combination of docking, molecular dynamics, and QSAR techniques, we identified potent inhibitors of the NS5-MTase protein. Our investigation identified a flavonoid exhibiting high binding affinity towards the MTase protein across major DENV serotypes. Conclusion Furthermore, molecular dynamics simulations and QSAR analysis were employed to assess the stability of molecular interactions and predicted activity, respectively; shedding light on the potential of the identified phytocompound with calculated IC50 of 76.009 nM as a therapeutic agent against MTase of DENV infection.
Keywords: Baicalin; Dengue; Methyltransferase; Molecular Dynamics simulations; QSAR; Virtual screening